Detection of stem cells in human endometrium: immune-histochemical study - Mejbel Hamad, Sameeah (Journal of Ideas in Health, 2022)
In this work, we recruited CD105 and CD90 markers to identify the endometrial stem cells (EnSCs) in the human uterine endometrium. Fifty endometrial specimens have been extracted from twenty-five deceased women. All specimens have been embedded in paraffin block and prepared for immune-histochemical processing. The expression of CD105 and CD90 was counted per high power field (HPF). Paired sample t-test was used to compare the means between groups and age variables. The Statistical analysis was conducted using “SPSS16 software" The statistical significance was considered at less than 0.05. Results of paired sample t-test showed that the expression count (EC) at the Basalis layer (with CD105) was 5.26 points higher than the Functionalis layer (95% CI [3.43, 7.09]) and the correlation was strongly and positively related (r = 0.829, P < 0.001). The EC at Basalis layer (with CD90) was 4.96 points higher than Functionalis layer (95% CI [3.02, 6.89]) and the correlation was strongly and positively related (r = 0.746, P= < 0.001). The EC at Functionalis layer (with CD105) was 0.9 points higher than the Stroma layer (95% CI [2.27, 4.11]); however, the correlation was weak and positively related (r = 0.429, P = 0.032). The EC at Functionalis layer (with CD90) was 1.4 points higher than the Stroma layer (95% CI [2.1, 4.2]), but the correlation was moderately and positively related r = 0.547, P = 0.005). Findings of an independent-sample t-test showed that the EC of stem cells at the Functionalis, Basalis, and Stroma layers (with CD105 and CD90 markers) was more among patients of reproductive age (<50 years) than patients who were at non-reproductive age (50 years and above), a statistically significant difference [(m = 9.6, 95% CI (5.3, 14.6), t (19.630) = 4.413, P < 0.001)], [(m = 10.2, 95% CI (5.2, 15.2), t (20.714) = 4.202, P < 0.001)] and [(m = 8.4, 95% CI (3.5, 13.4), t (12.313) = 3.523, P = 0.002)], respectively. In conclusion, the EC of the stem cells in the endometrium decreases with age.